Pentingnya Makanan Dengan Gizi Seimbang Guna Meningkatkan SDM Yang Unggul ( Olahan Makanan Sehat dari Daun Kelor ) - Nurbaiti, Nurbaiti; Indriani, Wiewiek; Listyaningsih, Erna; Putri, Nadia Tiara; Hasanah, Putri; Mariska, Novalia; Launi, Amalia Vika; Kurnia, Kurnia (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2022)
Human Resources (HR) is the most important factor and plays an important role in the development of an area or village. To realize superior human resources, it can be started from food with balanced nutrition, Food ingredients with good nutrition can be found around us, can be through vegetables, fruits, and wild plants such as Moringa leaves. Moringa leaves contain Protein, Iron and Vitamin C which are good for the body, but because it has a fairly pungent smell, people rarely like this plant. For that, people need to know how to manage Moringa leaves into food with balanced nutrition, and become processed that is favored by people. Everyone who later eats Moringa leaves is expected to be able to realize superior human resources.